Stock returns-bitcoin Nexus: evidence from pre and during Covid-19 outbreak / Bee-Hoong Tay - Tay, Bee Hoong (UiTM Cawangan Kedah, 2022)
The extant literature showed that interaction between cryptocurrency and stock markets was not comprehensively supported during the COVID-19 pandemic. This study aims to examine the relationship of bitcoin and international stock markets to evaluate how the role of cryptocurrency has changed over the COVID-19 period. Using the daily data of 12 international stock markets from the advanced economies and emerging economies, the study showed that cryptocurrency as measured by the price dynamics of bitcoin had more interactions with the international stock markets during the onset of COVID-19. Bitcoin was a hedge asset for the Japan stock market prior to COVID-19. In the period of COVID-19, bitcoin has important portfolio diversification implications for seven international stock market indices, i.e., US, UK, France, Germany, Thailand, India and Turkey, but it is neither a hedge asset nor safe haven for the remainder of the markets in advanced economies and emerging economies. The study further revealed that negative shocks have a larger effect on the conditional volatility of the stock than positive shocks in the observed samples and confirmed the existence of the asymmetric effect on the international stock markets during the pandemic COVID-19 period. This study contributes to complement the existing body of knowledge on the bitcoin and stock markets nexus pre and during the COVID-19 period.